Évaluation des effets de la télé-surveillance sur la criminalité commise dans 13 stations du métro de Montréal - Grandmaison, Rachel; Tremblay, Pierre (Criminologie, 1997)
This paper provides an assessment of the impact ofCCTV cameras on the monthly incidence of crimes committed in Montreal's underground subway network. Since 13 of the 65 Montreal's underground stations were provided with such cameras (about 10 on average per target station) between August 1991 and January 1993, we examined the monthly volume of reported offenses in both target and control stations between January 1991 and December 1993. Our analyses have been unable to detect any overall impact of CCTV cameras on the behavior of offenders. And controlling for kinds of crime or for specific areas and places within subway stations (depending on the location of cameras) did not change or qualify the initial overall no-effect finding.